2022
DOI: 10.3390/su142416775
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Environmental Pollution for Sustainable Development Goals—Evidence from Asian Countries

Abstract: The world is faced with climate change and gradual increases in seawater and carbon dioxide levels, and leaders of countries all over the world need to take action in order to achieve the Sustainable Development Goals (SDGs). This paper aims to identify the factors affecting environmental pollution in Asian countries for sustainable development. This study collected data from the World Bank covering 2000–2020 for 15 Asian countries. The data were processed via STATA 17.0; the study employed the unrestricted fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…However, the regression results show the relationship between ROE and SR quality. This issue is similar to previous studies by Thu et al (2022) when they argue that the ROE variable, representing profitability, is positively associated with all sustainability reporting variables. This problem can be explained by the fact that while ROE depends on the components of operating efficiency, capital structure, and risk, the quality of sustainability reporting depends on the sense of social responsibility of the business.…”
Section: Roe and Liquidity Analysissupporting
confidence: 90%
“…However, the regression results show the relationship between ROE and SR quality. This issue is similar to previous studies by Thu et al (2022) when they argue that the ROE variable, representing profitability, is positively associated with all sustainability reporting variables. This problem can be explained by the fact that while ROE depends on the components of operating efficiency, capital structure, and risk, the quality of sustainability reporting depends on the sense of social responsibility of the business.…”
Section: Roe and Liquidity Analysissupporting
confidence: 90%
“…Consequently, it is not conducive to the promotion of industrial transformation and upgrading. Another view is the dynamic level of "innovation compensation" [45,46]. As the degree of environmental decentralization increases, strict environmental regulations imposed by the government will increase the production costs of enterprises.…”
Section: Theoretical Mechanism Analysis and Research Hypothesismentioning
confidence: 99%
“…Thu et al investigated the factors that contribute to environmental pollution in Asia and Vietnam. They found that the greater the renewable consumption is, the better the environmental condition has in Vietnam and Asia [22,23]. Raihan et al referred to the connections that exist between green electricity consumption, the industrialization of the economy, forest area coverage, and CO2 in the Russian context [24,25].…”
Section: Literature Reviewmentioning
confidence: 99%